Quality Assessment of Electrical Equipment using ANOVA and Linear Regression Techniques - Nutu, Catalin Silviu (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The article concerns utilization of linear regression and analysis of variance (ANOVA) for a set of data regarding the quality of electrical equipment. More precisely, this set of data concerns the nonconformant housings of electric motors for different diameters of housings. Both statistical methods, linear regression and ANOVA are employed to analyse this data with regard to their linear dependency and to check whether this data is likely to come from groups with the same mean.